The psychological symptoms and behavioral problems of children with mothers working as medical staff in the crisis of Covid-19 outbreak in Hamadan, Iran - Raeisi, Roya; Gholamzad, Shakiba; Dehkordi, Mansoureh Kiani; Kheirabadi, Mehri Rezaei; Ddehkordi, Ali Hhasanpour; Sobhani, Mohammad Mahdi; Movahedi, Mahsa (Frontiers in Psychiatry, 2023)
Background and objectives The purpose of this study was to investigate the psychological symptoms and behavioral problems of children with mothers working as medical staff in the crisis of Covid-19 disease in Hamadan. Methods This descriptive causal-comparative study was conducted on all mothers with children aged 6 to 12 years in Hamadan from September 2 to November 29, 2020. In this study, eligible individuals were selected using random sampling and were assigned to two groups of mothers working as the medical staff and the control group. The research instruments included the Child Behavior Checklist (Achenbach) and the Child Symptom Inventory-4 (CSI-4). Results The results showed that the mean scores of psychological and behavioral symptoms of children in terms of group membership (group of mothers working in the medical staff and control group) had a significant difference. There was a significant difference between the mean scores of depression and aggression in children of the staff group and the control group meaning that for depression and aggression scores of children of the staff group are higher than children of the control group (p < 0.05). There was no significant difference between the mean anxiety scores and there was almost a significant difference between the attention scores of the staff group and the control group (p < 0.05). Conclusion Children whose mothers worked as medical staff during Covid-19 show more depression, attention, and aggression problems than children whose mothers do not work as medical staff.